Recursos audiovisuales y su incidencia en el aprendizaje significativo en los estudiantes de la escuela de educación básica “Miguel de Cervantes” cantón Baba, Provincia los Ríos. - Basurto Alcívar, Paula Rosaura (2017)
The present work was carried out to verify the problematic that exist in the School of Basic Education Miguel de Cervantes in the way that they do not use the Audiovisual Resources to obtain a significant of the students that through the use these resources that can employ In the classroom will facilitate the best understanding of contents. This situation has generated a low performance in the significant learning of students for that reason in the following chapters is a detailed way of variables the following proposal is established: Design a manual of audiovisual resources to strengthen meaningful learning in students of basic education.